Growth And Yield of Soybean Devon I Variety With Application of Cow Manure And Mycorrhiza - Daryanti; Teguh Supriyadi; Achmad Fatchul Aziez; Dwi Susilo Utami; Sukamto (Agricultural Science, 2020)
One of the environmentally friendly ways to increase soybean production was to use organic fertilizers and mycorrhiza. This study aimed to determine the effect of cow manure dose and a dose of mycorrhiza on the growth and yield of soybean varieties Devon I. The study was conducted in April to September 2019 in Teguhan village, Sragen Regency, altitude 86 masl, with the grumosol soil type. This study used a randomized block design Complete by a factor of two treatments, the first factor dose of cow manure consists of four levels ie K0 = 0 tonnes / ha, K1 = 5 tonnes / ha, K2 = 10 tonnes / ha, K3 = 15 ton / ha and a dose of mycorrhiza consists of three levels ie M0 = 0 g, M1 = 3 g, M2 = 6 g per plant. The use of fertilizer was reduced by half a dose recommendation. The results showed that the dose of cow manure significantly affected the growth and yield of soybean, the mycorrhiza dose had no significant effect on the growth and yield of soybean. The lowest productivity in this study in the treatment without cow manure (1.158 tonnes/ha) and the highest productivity in the treatment of cow manure is 15 tonnes/ha (1, 46 tonnes/ha).